The impact of the global financial crisis on profitability of the banking industry: A comparative analysis - G. Rod Erfani; Bijan Vasigh (Economies, 2018)
In this paper, the effects of the recent global financial crisis on efficiency and profitability of financial institutions were analyzed. In a comparative study, the impacts of the global financial crisis on the performance of Islamic and commercial banks were examined. The fundamental difference between Islamic and conventional banking is that Islamic banking is founded upon the ethical principles of Islamic tradition and law (Sharia). By utilizing a sample of eight Islamic banks and eleven commercial banks, the impact of the global financial crisis on efficiency and profitability of the banking sector was evaluated. This study covered the period from 2006 to 2013. The results of this research were obtained from the Altman Z-score model, ratio analysis, the data envelopment analysis (DEA) method, and the seemingly unrelated regression (SUR) model. The results show that during the study period, Islamic banks (IBs) managed to maintain their efficiency while most commercial banks (CBs) suffered a loss in their efficiency. Furthermore, this study found that the financial crisis did not have a significant impact on the profitability of Islamic banks.
Keywords: G00; G01; G20; 330; global financial crisis; Islamic banking; bank profitability